PERLINDUNGAN HUKUM TERHADAP KEPEMILIKAN HAK CIPTA ATAS LAGU YANG DIMANFAATKAN PADA INDUSTRI KARAOKE - Supradnyana, Dewa Made; Darmadha, I Nyoman; Sandi Sudarsana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015, 2015)
Copyright is an exclusive right granted to a creator (author) of the works of art.Intellectual property rights are property rights arising from intellectual ability or bornmanusia. HKI indeed make works that arise or born due to human intellectual abilitiesthat must be protected. Therefore, the author will explain What are the obstacles to thepayment of royalties to the composer of the song used in the karaoke industry. Theresearch is empirical research juridical law. obstacles in the payment of royalties to thesongwriter of the song used in the service industry karaoke, the royalty payments fromthe industry it is not all karaoke services provided or paid to the collective managementorganizations which is YKCI and Wami, and the use of some types of songs that may beconsidered or fit for use in a karaoke service industry must be selected in advance, sotake the time to wait for results from that a song.
Keywords: Copyright, Intellectual Property Rights, Royalties